Adaptation of the short multidimensional inventory lifestyle evaluation-confinement to Turkish: Validity and reliability study - YILDIZ ÖZER, AYSEL (My University, 2023)
Objective: The aim of this study is to investigate the validity and reliability of the Short Multidimensional Lifestyle Assessment-Isolation (SMILE-C) Questionnaire, which was developed to evaluate lifestyle multidimensionally during COVID-19 pandemic, in the Turkish sample. Method: The research was carried out 345 university students who were able to access the internet between April 2021-February 2022. Participants filled in the inquiry forms sent to them online. The construct validity with Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis; convergent-discriminant validity with Average Variance Extracted (AVE), Composite Reliability (CR), Maximum Squared Variance (MSV), Average Shared Square Variance (ASV); internal consistency with Cronbach’s α coefficient; test-retest reliability with intraclass correlation coefficient were evaluated. The Healthy Lifestyle Behaviors Scale-II (HPLP-II) and the International Physical Activity Questionnaire-Short Form (IPAQ-SF) were used to assess criterion validity. Results: Cronbach’s α was 0.74 and ICC2.1 was 0.86. The EFA showed a six-factor model and four items loaded on more than one factor. The fit index values confirmed a good fit (Root mean square error of approximation=0.052; Goodness of fit index=0.940; Adjusted goodness of fit index=0.914; Comparative fit index=0.924; Normed fit index=0.901). A statistically significant positive correlation was found between the total SMILE-C score and the total HPLP-II score and all its sub-dimensions; the total IPAQ-SF score and the total SMILE-C score and the healthy lifestyle behavior sub-dimension(p<0.001). AVE, CR, MSV, and ASV values supported the convergent-discriminant validity of the scale. Conclusion: The Turkish version of SMILE-C is a valid and reliable questionnaire that can assess lifestyle multidimensional manner.

Amaç: Bu çalışmanın amacı COVID-19 pandemi sürecinde yaşam tarzını çok boyutlu olarak değerlendirmek amacıyla geliştirilen Kısa Çok Boyutlu Yaşam Tarzı Değerlendirme-İzolasyon (SMILE-C) ölçeğinin Türk örnekleminde geçerlik ve güvenirliğini araştırmaktır. Yöntem: Araştırma Nisan 2021- Şubat 2022 tarihleri arasında interenete erişebilen 345 üniversite öğrencisinin ile gerçekleştirildi. Katılımcılar kendilerine gönderilen sorgulama formlarını çevirimiçi olarak doldurdu. Açımlayıcı Faktör Analizi (AFA) ve Doğrulayıcı Faktör Analizi ile yapı geçerliliği, ortalama açıklanan varyans (AVE), birleşik güvenirlik (CR), maksimum paylaşılan varyansın karesi (MSV), paylaşılan varyansın karesinin ortalaması (ASV) ile yakınsak-ıraksak geçerlik; Cronbach’s α katsayısı ile iç tutarlılık, sınıf içi korelasyon katsayısı (ICC2.1) ile Test-tekrar test güvenilirliği değerlendirildi. Sağlıklı Yaşam Biçimi Davranışları Ölçeği-II (HPLP-II) ve Uluslararası Fiziksel Aktivite Anketi-Kısa Formu (IPAQ-SF) ölçüt geçerliliğini değerlendirmek için kullanıldı. Bulgular: Cronbach’s α değeri 0.74 ve ICC2.1 değeri 0.86 idi. AFA, altı faktörlü bir model ve birden fazla faktöre yüklenen dört madde gösterdi. Uyum indeksi değerleri iyi uyumu doğruladı (Yaklaşık hataların ortalama karekökü=0.052; İyilik uyum indeksi=0.940; Düzeltilmiş iyilik uyum indeksi =0.914; Karşılaştırmalı uyum indeksi=0.924; Normlandırılmış uyum indeksi=0.901). SMILE-C toplam puanı ile HPLP-II ‘nin toplam puanı ve tüm alt boyutları; IPAQ-SF toplam puanı ile SMILE-C toplam puanı ve sağlıklı yaşam davranışı alt boyutu arasında istatistiksel olarak anlamlı pozitif yönde bir ilişki saptandı (p<0.001). AVE, CR, MSV, ASV değerleri ölçeğin yakınsak-ıraksak geçerliğini destekledi. Sonuç: SMILE-C ölçeğinin Türkçe versiyonu yaşam tarzını çok boyutlu değerlendirebilen geçerli ve güvenilir bir ank ettir.
Kısa çok boyutlu yaşam tarzı değerlendirmesi - izolasyon ölçeği Türkçe formu: Geçerlik ve güvenilirlik çalışması
Keywords: Pandemi; Yaşam Tarzı; Geçerlilik; Güvenilirlik; COVID-19; Pandemic; Lifestyle; Validity; Reliability